Current Status of Stem Cell-Derived Therapies for Parkinson’s Disease: From Cell Assessment and Imaging Modalities to Clinical Trials - Jang, Se Eun; Qiu, Lifeng; Chan, Ling Ling; Tan, Eng-King; Zeng, Li (Frontiers in Neuroscience, 2020)
Curative therapies or treatments reversing the progression of Parkinson’s disease (PD) have attracted considerable interest in the last few decades. PD is characterized by the gradual loss of dopaminergic (DA) neurons and decreased striatal dopamine levels. Current challenges include optimizing neuroprotective strategies, developing personalized drug therapy and minimizing side effects from the long-term prescription of pharmacological drugs used to relieve short-term motor symptoms. Transplantation of DA cells into PD patients’ brains to replace degenerated DA has the potential to change treatment paradigm. Herein, we provide updates on current progress in stem cell-derived DA neuron transplantation as a therapeutic alternative for PD. We briefly highlight cell sources for transplantation and focus on cell assessment methods such as identification of genetic markers, single cell sequencing and imaging modalities used to access cell survival and function. More importantly, we summarize clinical reports of patients who have underwent cell-derived transplantation in PD to better perceive lessons that can be drawn from past and present clinical outcomes. Modifying factors include 1) source of the stem cells, 2) quality of the stem cells, 3) age of the patient 4) stage of disease progression at the time of cell therapy, 5) surgical technique/practices, and 6) the use of immunosuppression. We await the outcomes of joint efforts in clinical trials around the world such as NYSTEM and CiRA to further guide us in the selection of the most suitable parameters for cell-based neurotransplantation in PD.